PROSPECTS AND ASPECTS OF ADVANCED POLYMERIC COMPOSITE MATERIALS INTRODUCTION IN ANTONOV AIRCRAFT STRUCTURES - Andrieiev, Oleksii (Proceedings of National Aviation University (archive), 2019)
The study represents analysis of the status of PCM introduction in the locally produced aircraft, briefly describes certification processes to be followed during introduction of new materials. It also describes the results of ANTONOV Company specialists work in the area of introduction of new advanced polymeric composites